Concentric, isometric, and eccentric contractions: Which dominates alpine skiing? - Minetti, A. (Science and Skiing VII, 2018)
Alpine ski mechanics, the understanding of which would allow us to predict muscle use, indicate zero as the lowest limit of extra negative work. Despite the environmental, experimental, and technical complexity of this motor activity, modern GPS, hi-res cartography, EMG and electrogoniometry, wireless loggers and drone technology allow a more accurate description of it. An energy analysis of descents on skis seems to indicate that less than 40-50% of the potential energy has to be dissipated by muscles via eccentric contractions. Measurement improvements in the next few years will allow us to evidence any positive work (concentric) contributing to increase a skier's kinetic energy at the end of a turn.